Argumentation and Inference: A Unified Approach - Christophe Fouqueré; Myriam Quatrini (Baltic International Yearbook of Cognition, Logic and Communication, 2013)
We propose in this paper to use Ludics as a unified framework for the analysis of dialogue and the reasoning system. Not only is Ludics a logical theory, but it may also be built by means of concepts of game theory. We first present the main concepts of Ludics. A design is an abstraction and a generalization of the concept of proof. Interaction between designs is equivalent to cut elimination or modus ponens in logical theories. It appears to be a natural means for representing dialogues and also for reasoning. A design is a set of sequences of alternate actions, similar to a move in game theory. We apply Ludics to argumentative dialogues. We discuss how to model the speech acts of argumentative dialogues in terms of dialogue acts. A dialogue act is given by a Ludics action together with the expression that reveals the action in a turn of speech. We show also how arguments may be stored in a commitment state used for reasoning. Finally we revisit an example of juridical dialogue that has been analyzed by Prakken in a different framework.
Keywords: logical theory; game theory; juridical dialogue